유체-구조 상호연성 해석을 위한 입자법 시뮬레이션 기술 개발 - 황성철(Sung-Chul Hwang); 박종천(Jong-Chun Park); 송창용(Chang-Yong Song); 김영훈(Young-Hun Kim) (Han-guk haeyang gonghak hoeji (Online), 2013)
Recently, some fluid-structure interaction (FSI) problems involving the fluid impact loads interacting with structures, such as sloshing, slamming, green-water, etc., have been considered, especially in the ocean engineering field. The governing equations for both an elastic solid model and flow model were originally derived from similar continuum mechanics principles. In this study, an elastic model based on a particle method, the MPS method, was developed for simulating the FSI problems. The developed model was first applied to a simple cantilever deflection problem for verification. Then, the model was coupled with the fluid flow model, the PNU (Pusan National University modified)-MPS method, and applied to the numerical investigation of the coupling effects between a cantilever and a mass of water, which has variable density, free-falling to the end of the cantilever.